Urban–rural differences in the nature and prevalence of mental ill‐health in adults with intellectual disabilities. (1st February 2012) - Kiani, R.; Tyrer, F.; Hodgson, A.; Berkin, N.; Bhaumik, S.
Abstract Background In the general population there are statistically significant urban–rural differences in the rate of common mental disorders. In people with intellectual disability (ID) no study has attempted to address this issue. Aims To compare the prevalence of mental illness, autism spectrum disorder (ASD) and behaviour disorder in people with ID living in urban areas with those living in rural areas. Methods Cross‐sectional study of 2713 individuals registered with an ID service. Participants were assigned to urban or rural groups using the Department for Environment Food and Rural Affairs rural/urban local authority classification for their district. The main outcome variable was a clinical diagnosis of mental illness, ASD and behaviour disorder. Differences between diagnoses of mental illness in urban and rural areas were evaluated using the chi‐squared test for the difference in two independent proportions. Results No differences were observed between gender, age and level of ID of service users based on their place of residence. But more people from an ethnic minority background were living in urban areas than rural areas. No differences were observed in the overall prevalence of mental illness by place of residence. However, the results showed that ASD was more common in people living in rural areas. Conclusions We found these results surprising and at odds with the majority of studies carried out in the general population and propose several reasons for the differences found. We believe that the results and further studies in this area will help inform health service provision for those with ID who live in different geographical areas.